2018
DOI: 10.1007/s10096-018-3402-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and secondary care utilisation in a primary care population with non-tuberculous mycobacterial disease in the UK

Abstract: Prior research has identified risk factors associated with developing non-tuberculous mycobacterial disease (NTMD); we identified risk factors and secondary care utilisation of NTMD patients in the UK. This was a matched case-control study using electronic healthcare records from Clinical Practice Research Datalink from 2006 to 2016. NTMD was defined using prescription data and Read codes, based on international guidelines. Risk factors for NTMD were investigated using conditional logistic regression within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Over the last decades it has become apparent that several groups of individuals are prone to PNTM disease (Figure 1). These include patients with both genetic or acquired structural lung diseases such as cystic fibrosis (CF), chronic obstructive pulmonary disease (COPD), non-CF bronchiectasis, alpha-1 antitrypsin deficiency, previous pulmonary tuberculosis, and lung cancer (16)(17)(18). Patients with immune suppression due to primary immune deficiency syndromes (PIDs) such as Mendelian Susceptibility to Mycobacterial Disease (MSMD) associated with IL12-p40, IL12, IFNγ receptor abnormalities and gene deformities (IFNγR1, IFNγR2, IL12RB1, IL12B, STAT1, IKBKG, CYBB, ISG15, IRF8, GATA2) are at high risk of NTM infection (19)(20)(21).…”
Section: Risk Groups For Ntm Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decades it has become apparent that several groups of individuals are prone to PNTM disease (Figure 1). These include patients with both genetic or acquired structural lung diseases such as cystic fibrosis (CF), chronic obstructive pulmonary disease (COPD), non-CF bronchiectasis, alpha-1 antitrypsin deficiency, previous pulmonary tuberculosis, and lung cancer (16)(17)(18). Patients with immune suppression due to primary immune deficiency syndromes (PIDs) such as Mendelian Susceptibility to Mycobacterial Disease (MSMD) associated with IL12-p40, IL12, IFNγ receptor abnormalities and gene deformities (IFNγR1, IFNγR2, IL12RB1, IL12B, STAT1, IKBKG, CYBB, ISG15, IRF8, GATA2) are at high risk of NTM infection (19)(20)(21).…”
Section: Risk Groups For Ntm Diseasementioning
confidence: 99%
“…A multicentre study of MAC infection across Canada, France, Germany and the UK conducted in 2018 showed average direct medical costs per person year ranged from $US12,200 in Canada to $US25,500 in France (71). In addition to direct disease related costs, patients were also shown to have six times higher secondary care utilization events for disease-related and disease-unrelated illnesses (18).…”
Section: The Treatment Complications and Economic Burden Of Ntmmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk of NTM-LD is also increased in the elderly [38]. A history of pulmonary TB has also been reported as an important risk factor for NTM-LD in countries such as France, Denmark and the UK [39][40][41], as well as in regions with high prevalence of pulmonary TB [27][28][29]. There is no evidence of human-to-human transmission of MAC.…”
Section: Patients At Riskmentioning
confidence: 99%
“…Open access box 1 Factors which increase the risk of developing non-tuberculous mycobacterial pulmonary disease [12][13][14][15][16][17][18][19][20][21] ► Alcohol misuse ► Biological agents ► Chronic kidney disease ► Diabetes ► Female gender ► Gastro-oesophageal reflux disease ► Immunocompromise, primary or secondary to disease or drug therapies ► Inhaled corticosteroids ► Low body mass index ► Pneumoconiosis ► Underlying structural lung disease, for example, bronchiectasis, and COPD (chronic obstructive pulmonary disease) gastro-oesophageal reflux disease (GORD). Chest X-rays carried out by the COPD team look generally similar to previous imaging, though occasional nodularity that appeared to resolve on repeat imaging was noted.…”
Section: Case: a 67-year-old Slim-build Woman With A History Of Smokimentioning
confidence: 99%